2004
DOI: 10.1364/ao.43.001515
|View full text |Cite
|
Sign up to set email alerts
|

Linear dichroism of the cornea

Abstract: The dichroic properties of in vitro sheep corneas were studied with a spectrophotometer in transmission mode for several angles of incidence of light beams. Several models of corneal anisotropy have been presented in the literature. The results presented here allow us to believe that the cornea behaves as a dichroic biaxial crystal. Furthermore, this dichroism is weak when the angle of incidence on the corneal surface stays small. The mathematical model that describes these optical properties of the cornea use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Measurements by Louis-Dorr et al [63] using an incomplete polarimeter on excised sheep corneas showed that corneal dichroism is extremely weak.…”
Section: Corneamentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements by Louis-Dorr et al [63] using an incomplete polarimeter on excised sheep corneas showed that corneal dichroism is extremely weak.…”
Section: Corneamentioning
confidence: 99%
“…In the case of the cornea, polarization effects are due to the sheets of stacked collagen fibril lamellae of different orientations which are present in the stroma. The cylindrical fibers, stacked in an interfiber medium of lower refractive index, give rise to both linear form birefringence (retardance) [53] and form dichroism (diattenuation) [63]. van Blockland and Verhelst found that the cornea behaves as a biaxial crystal with the fast axis normal to the surface and the slow axis pointing nasally downward [28].…”
Section: Corneamentioning
confidence: 99%
See 1 more Smart Citation
“…Dichroism is an anisotropy of spectral absorption that manifests in changes in the amplitude of the electric vector of the polarized light [23,27,[33][34][35]. Dichroic macromolecules absorb polarized light differently according to the direction of their chromophoric groups in relation to the plane polarized light (PPL) [23,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of developing our understanding of refractive status and its relation to vision is to use animals eyes, both for general comparisons and to develop or evaluate procedures (for example, for refractive surgery) that would not be easy to undertake on human eyes in vivo . Such ex vivo studies to assess the structural effects of incisions, trephine application or laser pulses to the cornea, have been carried out on ovine eyes, as have some studies of the optical properties of the cornea . Corneal thickness must be considered as an important factor in such assessments but only one of these studies provides this information .…”
mentioning
confidence: 99%